A Population-based Study of Survival Impact of New Targeted and Immune-based Therapies for Metastatic or Unresectable Melanoma. Issue 10 (October 2018) - Hanna, T.P.; Nguyen, P.; Baetz, T.; Booth, C.M.; Eisenhauer, E.
Abstract: Aims: New targeted drugs and immune therapies reported since 2010 for metastatic or unresectable melanoma (MM) have shown improved survival in randomised trials. We studied the uptake of these new drugs and their impact on population-based survival. Materials and methods: This was a retrospective, population-based cohort study of all patients treated for MM in Ontario 2007–2015. Provincial administrative sources covering the whole population identified palliative systemic therapy, radiotherapy and metastasis surgery. Temporal trends in utilisation and survival were investigated, as was survival of treatments predefined as 'new drugs' (BRAF or MEK inhibitors, anti-CTLA4 and anti-PD-1 antibodies). Results: We identified 2793 treated MM patients. First treatment was systemic therapy (46%), radiotherapy (41%) and metastasis surgery (14%). Systemic treatment increased from 53% of patients (2007) to 75% (2015). New drug treatments increased from <6% of known first-line regimens in 2007 to 82% in 2015. One and 2 year overall survival was 28% and 15%, respectively, for all MM 2007–2009, rising to 46% and 35% for 2014–2015 (adjusted hazard ratio 0.56, 95% confidence interval 0.49–0.63, P < 0.0001). Survival gains were observed primarily among those cases initially treated with systemic therapy, which became dominated by the use of new drugs over the study period (2 year overall survival 16% 2007–2009 versus 44% 2014–2015; adjusted hazard ratio 0.46, 95% confidence interval 0.38–0.56, P < 0.0001). Conclusions: Utilisation of new targeted drugs and immune therapies for MM has increased considerably in routine practice 2007–2015. Consistent with the results of clinical trials, adoption was associated with substantial increases in survival of patients in the general population. Highlights: Population-based study of targeted drugs and immunotherapy for metastatic/unresectable melanoma. There was a dramatic shift towards use of immunotherapy and targeted therapy over time. Two-year overall survival for the whole population more than doubled from 2007-2009 to 2014-2015. Greatest absolute survival difference was among cases first treated with systemic therapy. Clinically and statistically significant differences in survival were observed in adjusted analysis.